Global health education in the Dutch Caribbean: 50 years of a unique Groningen-Curaçao clinical clerkship program - Ashley J Duits; Jan B Kuks; Jamiu O Busari (Inishmore Laser Scientific Publishing Ltd, 2020)
The globalization of healthcare has had a significant impact on healthcare delivery and human workforce development in many countries. Consequently, many educational institutions have had to revise the content of their medical curricula to focus on training and preparing future doctors to effectively cater to the needs of the "modern patient". The focus covers broader aspects of medicine that include environmental and professional culture and the impact of socioeconomic inequalities on the delivery of healthcare. Therefore, in most global health (GH) education programs described, students undertake a specific part of their clinical rotation in a foreign (non-western) educational setting to facilitate authentic learning experiences within a resource-constrained environment. In this paper we present a unique Global Health program for medical interns between the University Medical Center Groningen, Netherlands and the Sint Elisabeth Hospital, Curaçao, Dutch Caribbean that has, for more than 50 years, been providing a one-year internship program as part of the formal Groningen curriculum. The program we describe, illustrates the essential requirements for best practice in GH education that fully complies with recently proposed GH program objectives and competencies. The characteristics of our long running program show the basic requirements necessary for sustainable and successful health education collaboration between institutions in high- and low/middle income countries. Finally, this program, which is part of a Dutch medical curriculum, not only provided unique global health learning experiences for the interns, but importantly also contributed to improving the general healthcare delivery services on the island of Curaçao as well.